Landscape‐scale population connectivity in two parasitoid species associated with the spruce budworm: Testing the birdfeeder effect using genetic data. Issue 22 (12th September 2021) - Legault, Simon; Wittische, Julian; Cusson, Michel; Brodeur, Jacques; James, Patrick M. A.
Abstract: Periodic and spatially synchronous outbreaks of insect pests have dramatic consequences for boreal and sub‐boreal forests. Within these multitrophic systems, parasitoids can be stabilizing agents by dispersing toward patches containing higher host density (the so‐called birdfeeder effect). However, we know little about the dispersal abilities of parasitoids in continuous forested landscapes, limiting our understanding of the spatiotemporal dynamics of host–parasitoid systems, and constraining our ability to predict forest resilience in the context of global changes. In this study, we investigate the spatial genetic structure and spatial variation in genetic diversity of two important species of spruce budworm larval parasitoids during outbreaks: Apanteles fumiferanae Viereck (Braconidae) and Glypta fumiferanae (Viereck) (Ichneumonidae). Using parasitoids sampled in 2014 from 26 and 29 locations across a study area of 350, 000 km 2, we identified 1, 012 and 992 neutral SNP loci for A . fumiferanae ( N  = 279 individuals) and G .  fumiferanae ( N  = 382), respectively. Using DAPC, PCA, AMOVA, and IBD analyses, we found evidence for panmixia and high genetic connectivity for both species, matching the previously described genetic structure of the spruce budworm within the same context, suggesting similar effective dispersal during outbreaks and high parasitoid population densities between outbreaks. We also found a significant negative relationship between genetic diversity and latitude for A . fumiferanae but not for G . fumiferanae, suggesting that northern range limits may vary by species within the spruce budworm parasitoid community. These spatial dynamics should be considered when predicting future insect outbreak severities in boreal landscapes.